Thermoelastic modelling of the skin at finite deformations. (December 2016) - McBride, A.; Bargmann, S.; Pond, D.; Limbert, G.
Abstract: The modelling and computation of the coupled thermal and mechanical response of human skin at finite deformations is considered. The model extends current thermal models to account for thermally- and mechanically-induced deformations. Details of the solution of the highly nonlinear system of governing equations using the finite element method are presented. A representative numerical example illustrates the importance of considering the coupled response for the problem of a rigid, hot indenter in contact with the skin. Abstract : Highlights: Present a model for thermoelastic response of skin at finite deformations. Extend existing models of biological heat conduction to finite deformations. Give details of the numerical solution using finite element method. Illustrate theory with a representative numerical example.